Preparation method of anode catalyst layer, anode catalyst layer and fuel cell
By using an anode catalytic layer combined with WO3 film and Pt nanoparticles, the problem of insufficient durability of fuel cell electrode catalysts is solved, and high-performance and long-life fuel cell operation is achieved, corrosion of carbon support is avoided and the stability of the catalyst is improved. sex.
Patent Information
- Application Number
- CN202411021651.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2024-12-13
AI Technical Summary
The durability of fuel cell electrode catalysts is insufficient, especially the corrosion of carbon support carriers under harsh conditions leads to reduced performance. The existing high-platinum-loaded materials are prone to aggregate on functionalized carbon nanotubes and graphene, which fails to effectively solve the problem of carbon corrosion.
Using WO3 film as the anode catalyst support, oxygen vacancies are generated through plasma surface treatment and Pt nanoparticles are deposited, ionic polymer solution is added to form a Pt/p-WO3 anode catalytic layer, avoiding the use of easily corrosive carbon support and overflowing through hydrogen The effect provides additional hydrogen ions and electrons, improving the durability of the catalyst.
It significantly improves the durability of the anode catalyst, avoids corrosion of carbon support, enhances the stability and performance of the catalyst, and achieves low-cost and high-performance fuel cell operation.
Smart Images

Figure CN119133471A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fuel cell technology, and in particular to a method for preparing an anode catalyst layer, an anode catalyst layer and a fuel cell. Background Art
[0002] In recent years, the global energy crisis and environmental pollution have become increasingly serious, and countries around the world have begun to vigorously develop renewable energy. Among the many renewable energy sources, hydrogen energy has attracted widespread attention due to its high energy density, theoretical reaction product is only water, clean and environmentally friendly, and wide sources. In the current new energy vehicles aimed at solving the problems of global energy consumption and greenhouse gas emissions, fuel cells play a vital role in obtaining the electrical energy stored in molecular chemical bonds due to their high efficiency and fuel flexibility.
[0003] However, the poor catalyst durability of fuel cell electrodes has hindered the wider technical deployment of fuel cells. In actual fuel cell electric vehicle operation under various harsh conditions, polymer electrolyte membrane fuel cells show significantly reduced performance due to corrosion of the carbon support carrier. A large number of experiments have been carried out to develop corrosion-resistant carriers. Although carbon nanotubes (CNTs), graphene and other graphitized materials with more stable structures than carbon black have been used, high platinum loading on unfunctionalized carbon nanotubes and graphene is prone to aggregation, and a fundamental solution to carbon corrosion has not yet been provided, resulting in performance degradation of fuel cells. Therefore, how to improve the durability of the anode catalyst layer is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The present application provides a method for preparing an anode catalyst layer, an anode catalyst layer and a fuel cell to solve the following technical problem: how to improve the durability of the anode catalyst layer.
[0005] In a first aspect, the present application provides a method for preparing an anode catalyst layer, the method comprising:
[0006] Obtain WO3 thin film;
[0007] activating the WO3 film to generate oxygen vacancies in the WO3 lattice to obtain a p-WO3 film;
[0008] Depositing Pt nanoparticles on at least a portion of the surface of the p-WO3 film to obtain a Pt / p-WO3 film;
[0009] The ionic polymer solution is dispersed into the Pt / p-WO3 thin film to obtain a Pt / p-WO3 anode catalyst layer.
[0010] Optionally, the step of obtaining the WO3 thin film comprises:
[0011] Mixing WO3 nanopowder with anhydrous ethanol to obtain WO3 slurry;
[0012] The WO3 slurry is coated on at least a portion of the surface of the base film, and then dried to obtain a WO3 thin film.
[0013] Optionally, the mass ratio of the WO3 nanopowder to the anhydrous ethanol is 1:1 to 1:10.
[0014] Optionally, the activation adopts plasma surface treatment.
[0015] Optionally, the plasma gas source of the plasma surface treatment includes one or more of O2, Ar, H2 and N2, and the plasma surface treatment includes the following parameters: the flow rate of the plasma gas source is 10sccm~30sccm, the RF plasma power is 150W~200W, and the chamber pressure is ≤30mTorr.
[0016] Optionally, the step of depositing Pt nanoparticles on at least a portion of the surface of the p-WO3 film to obtain a Pt / p-WO3 film comprises:
[0017] Placing the p-WO3 film in a deposition chamber of a plasma enhanced atomic layer deposition device;
[0018] Under vacuum conditions, adsorbing a platinum precursor onto the surface of the p-WO3 film;
[0019] Filling the deposition chamber with an inert gas for purging;
[0020] Passing an oxygen precursor into the deposition chamber to undergo an adsorption reaction with the platinum precursor to obtain the p-WO3 film containing a deposited platinum layer;
[0021] Filling the deposition chamber with an inert gas for purging;
[0022] The above steps are repeated to obtain a Pt / p-WO3 thin film with a set platinum layer thickness.
[0023] Optionally, the platinum precursor is trimethyl(methylcyclopentadienyl)platinum, and the oxygen precursor is O2 plasma.
[0024] Optionally, the temperature of the deposition chamber is 120°C to 160°C, and the temperature of the platinum precursor is maintained at 65°C to 85°C.
[0025] In a second aspect, the present application provides an anode catalyst layer prepared by the method described in any one of the embodiments in the first aspect.
[0026] In a third aspect, the present application provides a fuel cell, comprising the anode catalyst layer described in the embodiment of the second aspect.
[0027] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0028] The present application provides a method for preparing an anode catalyst layer, comprising: obtaining a WO3 film; activating the WO3 film to generate oxygen vacancies in the WO3 lattice to obtain a p-WO3 film; depositing Pt nanoparticles on at least a portion of the surface of the p-WO3 film to obtain a Pt / p-WO3 film; and dispersing an ionic polymer solution into the Pt / p-WO3 film to obtain a Pt / p-WO3 anode catalyst layer. By using WO3 as an anode catalyst carrier, the use of a corrosive carbon carrier is avoided, thereby avoiding the problem of easy corrosion caused by the carbon carrier. At the same time, WO3 can generate H through the hydrogen spillover effect. x WO3,H x The decomposition of WO3 can provide additional hydrogen ions and electrons, which can avoid insufficient hydrogen supply at the anode, thereby avoiding the reverse polarity phenomenon, and then avoiding serious corrosion of the anode catalyst, greatly improving the durability of the catalyst; by activating the WO3 film, a large number of oxygen vacancies are generated in the WO3 lattice, reducing the resistance of the WO3 film, and improving the surface reactivity of WO3, thereby facilitating the uniform deposition of Pt, which is beneficial to improving the catalytic activity of Pt; by adding an ion polymer solution, the dispersion of platinum particles and the transmission of protons are promoted. The anode catalyst prepared in this way has long durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0030] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0031] Figure 1 A schematic diagram of a process for preparing an anode catalyst layer provided in an embodiment of the present application;
[0032] Figure 2 This is a reverse polarization curve diagram of the Pt / p-WO3 anode catalyst layer provided in Example 1 of the present application;
[0033] Figure 3Polarization curve diagram of the anode catalyst layer provided for Example 1 and the comparative example of the present application. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0035] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0036] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "the following at least one item (items)" or similar expressions refer to any combination of these items, including any combination of single items (items) or plural items (items). For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or plural, respectively.
[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0038] The creative concept of this application is:
[0039] In the actual operation of fuel cells, the carbon support in the Pt / C catalyst in the membrane electrode (MEA) of the proton exchange membrane fuel cell (PEMFC) will be corroded when the membrane electrode (MEA) is repeatedly started / shutdown (SU / SD) and the fuel is insufficient, resulting in the performance degradation of the fuel cell. The more specific reason is that when the PEMFC undergoes excessive load changes and a momentary shortage of hydrogen fuel occurs in the stack, the anode carbon support reacts with water to meet the required power. During the SU / SD cycle, the chemical potential of the cathode briefly exceeds 1.5V due to anode air permeation, but the carbon support is exposed to an oxidizing environment, thereby increasing cathode corrosion. As a result, the Pt catalyst particles separate from the carbon support and undergo a process called Ostwald ripening, in which fine particles agglomerate with nearby large particles. This causes the Pt catalyst to gradually aggregate into huge particles. Ultimately, the electrochemical reaction sites decrease with a significant reduction in the three-phase boundary, and it becomes difficult to transport reactants due to the physical coverage of large mass particles, which in turn leads to the performance degradation of the fuel cell.
[0040] In order to solve the above technical problems, the present application creatively uses WO3 as the anode catalyst carrier, thereby avoiding the use of easily corrosive carbon carriers, thereby avoiding the easy corrosion problem caused by carbon carriers. At the same time, WO3 can produce tungsten bronze (H x WO3), H x The decomposition of WO3 can provide additional hydrogen ions and electrons, which can avoid insufficient hydrogen supply to the anode, thus avoiding the phenomenon of the single cell voltage being lower than zero volts (reverse polarity), thereby avoiding serious corrosion of the anode catalyst and greatly improving the durability of the catalyst. x WO3 can also remove oxygen that penetrates or passes through the anode during startup / shutdown. The specific reaction equation is 4H x WO y +xO2→4WO y+2xH2O, avoid unstable battery potential and prevent cathode corrosion, thereby stabilizing the battery potential. At the same time, in order to compensate for the low electrical conductivity of metal oxides that may lead to initial performance degradation, the present application performs plasma surface treatment on the WO3 layer, and forms Pt nanoparticles by atomic layer deposition to prepare extremely stable anode catalysts with low Pt loading. Ultimately, compared with commercial Pt / C anode catalyst layers, the Pt / p-WO3 anode catalyst layer prepared by the present application shows the advantages of low cost, high performance, long durability and anti-reverse polarity ability under various working conditions.
[0041] Figure 1 A schematic flow chart of a method for preparing an anode catalyst layer provided in an embodiment of the present application.
[0042] See also Figure 1 The present application provides a method for preparing an anode catalyst layer, the method comprising:
[0043] S1, obtain WO3 thin film;
[0044] In some embodiments, the step of obtaining a WO3 thin film comprises:
[0045] S101, mixing WO3 nano powder with anhydrous ethanol to obtain WO3 slurry;
[0046] S102, coating the WO3 slurry on at least a portion of the surface of the base film, and then drying to obtain a WO3 thin film.
[0047] It should be noted that the base film may be a polyimide film, and during the process of preparing MEA by hot pressing, the polyimide film may be removed by transfer technology.
[0048] In some embodiments, the mass ratio of the WO3 nanopowder to the anhydrous ethanol is 1:1 to 1:10.
[0049] In the above embodiment, the mass ratio of WO3 nanopowder to anhydrous ethanol is controlled, on the one hand, to ensure that the WO3 nanopowder is fully dispersed in the anhydrous ethanol, and on the other hand, in the subsequent drying process, the volatilization time of the ethanol is not too long. Exemplarily, the mass ratio of WO3 nanopowder to anhydrous ethanol can be 1:1, 1:2, 1:4, 1:6, 1:8, 1:10, etc.
[0050] S2, activating the WO3 film to generate oxygen vacancies in the WO3 lattice to obtain a p-WO3 film;
[0051] In some embodiments, the activation employs plasma surface treatment.
[0052] In the above embodiment, during the plasma surface treatment, a large number of oxygen vacancies are generated in the WO3 lattice, thereby increasing the Fermi level of the WO3 film and reducing the band gap energy. At the same time, due to the reduced band gap energy, the activated p-WO3 film has the same low resistance property as the n-type semiconductor. Therefore, plasma surface treatment can solve the problem of high resistance of WO3. At the same time, plasma surface treatment breaks the inert state of WO3, thereby improving the surface reactivity of WO3, and then facilitating the deposition of Pt. Therefore, plasma surface treatment on the WO3 layer makes up for the problem that the low conductivity of the metal oxide may cause initial performance degradation.
[0053] In some embodiments, the plasma gas source of the plasma surface treatment includes one or more of O2, Ar, H2 and N2, and the plasma surface treatment includes the following parameters: the flow rate of the plasma gas source is 10sccm~30sccm, the RF plasma power is 150W~200W, and the chamber pressure is ≤30mTorr.
[0054] In the above embodiment, the RF power directly affects the plasma concentration, and the flow rate of the plasma gas source, the RF plasma power and the chamber pressure are controlled to ensure the full activation of the WO3 film. For example, the flow rate of the plasma gas source can be 10sccm, 15sccm, 20sccm, 25sccm, 30sccm, etc., the RF plasma power can be 150W, 160W, 170W, 180W, 190W, 200W, etc., and the chamber pressure can be 10mTorr, 15mTorr, 20mTorr, 25mTorr, 30mTorr, etc.
[0055] S3, depositing Pt nanoparticles on at least a portion of the surface of the p-WO3 film to obtain a Pt / p-WO3 film;
[0056] In some embodiments, the step of depositing Pt nanoparticles on at least a portion of the surface of the p-WO3 film to obtain a Pt / p-WO3 film comprises:
[0057] S301, placing the p-WO3 film in a deposition chamber of a plasma enhanced atomic layer deposition device;
[0058] S302, adsorbing a platinum precursor onto the surface of the p-WO3 film under vacuum conditions;
[0059] S303, filling the deposition chamber with an inert gas for purging;
[0060] S304, introducing an oxygen precursor into the deposition chamber to undergo an adsorption reaction with the platinum precursor to obtain the p-WO3 film containing a deposited platinum layer;
[0061] S305, filling the deposition chamber with an inert gas for purging;
[0062] S306, repeat the above steps to obtain a Pt / p-WO3 thin film with a set platinum layer thickness.
[0063] It should be noted that the plasma enhanced atomic layer deposition device (PEALD) is mainly composed of a deposition chamber, a plasma source, a reaction gas supply system and a control system. The high-speed Ar gas allows the platinum precursor to be filled into the deposition chamber in a pulsed manner, and then saturated adsorption is performed on the surface of the p-WO3 film. The reaction gas O2 is used to react with the platinum precursor adsorbed on the surface of the p-WO3 film in the cavity to generate platinum, and the reaction is repeated to deposit a platinum film in the cavity. At the same time, even if a highly active plasma is used as a reactant at low temperatures, plasma enhanced atomic layer deposition can also obtain high-purity metals. The plasma enhanced atomic layer deposition method provided in this application ensures that Pt is evenly distributed on a nanoscale, and on the premise of using a small amount of precious metal Pt, the catalytic activity is maximized. Therefore, the Pt / p-WO3 anode catalyst layer synthesized by plasma enhanced atomic layer deposition has the advantages of low cost, high performance and long durability.
[0064] In some embodiments, the platinum precursor is trimethyl(methylcyclopentadienyl)platinum, and the oxygen precursor is O2 plasma.
[0065] In some embodiments, the temperature of the deposition chamber is 120°C to 160°C, and the temperature of the platinum precursor is maintained at 65°C to 85°C.
[0066] In the above embodiment, the precursor temperature affects the deposition rate. Controlling the temperature of the deposition chamber and the temperature of the platinum precursor can, on the one hand, ensure the deposition rate of platinum, and on the other hand, avoid the decomposition failure of the platinum precursor. At the same time, the temperature of the deposition chamber is also the deposition temperature. Exemplarily, the temperature of the deposition chamber can be 120°C, 130°C, 140°C, 150°C, 160°C, etc., and the temperature of the platinum precursor can be maintained at 65°C, 70°C, 75°C, 80°C, 85°C, etc.
[0067] In some embodiments, the inert gas is Ar gas, and the purging time is 60s to 120s.
[0068] S4, dispersing the ionic polymer solution into the Pt / p-WO3 film to obtain a Pt / p-WO3 anode catalyst layer.
[0069] It should be noted that adding an ionic polymer solution to the Pt / p-WO3 film can promote the dispersion of platinum particles and the transmission of protons, increase the active area of the catalyst, and reduce its ohmic impedance, thereby effectively improving the utilization rate of the catalyst.
[0070] In some embodiments, the solute of the ionic polymer solution is 10% by mass of water-based Nafion ionomer (DuPont, USA), the solvent is ethanol, and the volume ratio of the water-based Nafion ionomer to ethanol is 1:15 to 1:20.
[0071] Based on a general inventive concept, the present application provides an anode catalyst layer prepared by the method described in any one of the above embodiments.
[0072] The anode catalyst layer is realized based on the preparation method of the anode catalyst layer. The specific steps of the preparation method of the anode catalyst layer can refer to the above-mentioned embodiment. Since the anode catalyst layer adopts part or all of the technical solutions of the above-mentioned embodiment, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.
[0073] Based on a general inventive concept, the present application provides a fuel cell, which includes the anode catalyst layer described in the above embodiments.
[0074] It should be noted that the fuel cell generally refers to a proton exchange membrane fuel cell.
[0075] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0076] Example 1
[0077] This embodiment provides a method for preparing an anode catalyst layer, comprising the following steps:
[0078] S11, 2000 mg of WO3 nanopowder was mixed with 4000 mg of anhydrous ethanol, and ultrasonically dispersed for 30 min to obtain WO3 slurry; the WO3 slurry was coated on the surface of a polyimide film with a thickness of 25 μm using a scraper, and then dried in an oven at 70° C. for 20 h to obtain a WO3 thin film;
[0079] S21, subjecting the WO3 film to Ar plasma surface treatment to generate oxygen vacancies in the WO3 lattice to obtain a p-WO3 film; wherein the RF plasma power is 200 W, the Ar flow rate is 20 sccm, and the chamber pressure is set to 30 mTorr;
[0080] S31, placing the p-WO3 film in a deposition chamber of a customized plasma enhanced atomic layer deposition device (PEALD), under vacuum conditions, using a precursor pulse consisting of PEALD and trimethyl (methylcyclopentadienyl) platinum (IV) (MeCpPtMe3) for 1s, adsorbing trimethyl (methylcyclopentadienyl) platinum (IV) onto the surface of the p-WO3 film, filling the deposition chamber with Ar gas for 60s of purge, introducing O2 plasma into the deposition chamber to react with trimethyl (methylcyclopentadienyl) platinum (IV) for adsorption, and obtaining a p-WO3 film containing a deposited platinum layer, filling the deposition chamber with Ar gas for 60s of purge, and repeating the above steps to obtain a Pt / p-WO3 film having a preset platinum layer thickness; wherein, O2 plasma is generated using O2 (50sccm) with a radio frequency plasma power of 250W;
[0081] S41. Use a micropipette to disperse 40 μL of a mixed solution of 10 wt% water-based Nafion ionomer (DuPont, USA) and ethanol in a volume ratio of 1:16 on the Pt / p-WO3 film, and dry it in an oven at 70°C for 24 hours to obtain a Pt / p-WO3 anode catalyst layer.
[0082] Based on the above-mentioned Pt / p-WO3 anode catalyst layer, this embodiment also provides a method for preparing a fuel cell, comprising the following steps:
[0083] 530 mg of 40 wt% Pt / C, 2600 mg of 10 wt% water-based Nafion ionomer and 8000 mg of isopropyl alcohol (IPA) were mixed for 15 min to obtain Pt / C slurry. The Pt / C slurry was coated on the surface of a polyimide membrane with a thickness of 25 μm using a 150 μm wire rod and dried at 70 ° C for 24 h to obtain a Pt / C cathode catalyst layer; the Pt / p-WO3 anode catalyst layer and the Pt / C cathode catalyst layer were cut into 5×5 cm 2 The cell area. At 130°C and 380kPa, the proton exchange membrane (Gore 8μm membrane), Pt / p-WO3 anode catalyst layer, and Pt / C cathode catalyst layer were hot pressed to prepare a membrane electrode; the obtained membrane electrode and diffusion layer (Toray carbon paper Toray GDL gas diffusion layer 055) and sealing ring were assembled into a single cell test fixture to obtain a single cell.
[0084] Example 2
[0085] This embodiment provides a method for preparing an anode catalyst layer, comprising the following steps:
[0086] S11, 2000 mg of WO3 nanopowder was mixed with 8000 mg of anhydrous ethanol, and ultrasonically dispersed for 60 min to obtain WO3 slurry; the WO3 slurry was coated on the surface of a polyimide film with a thickness of 25 μm using a scraper, and then dried in an oven at 60° C. for 30 h to obtain a WO3 thin film;
[0087] S21, subjecting the WO3 film to Ar plasma surface treatment to generate oxygen vacancies in the WO3 lattice to obtain a p-WO3 film; wherein the RF plasma power is 180 W, the Ar flow rate is 30 sccm, and the chamber pressure is set to 25 mTorr;
[0088] S31, placing the p-WO3 film in a deposition chamber of a customized plasma enhanced atomic layer deposition device (PEALD), using a precursor pulse composed of PEALD and trimethyl (methylcyclopentadienyl) platinum (IV) (MeCpPtMe3) for 2s under vacuum conditions, adsorbing trimethyl (methylcyclopentadienyl) platinum (IV) onto the surface of the p-WO3 film, filling the deposition chamber with Ar gas for 120s of purge, introducing O2 plasma into the deposition chamber to react with trimethyl (methylcyclopentadienyl) platinum (IV) for adsorption, and obtaining a p-WO3 film containing a deposited platinum layer, filling the deposition chamber with Ar gas for 60s of purge, and repeating the above steps to obtain a Pt / p-WO3 film having a preset platinum layer thickness; wherein, O2 plasma is generated using O2 (50sccm) with a radio frequency plasma power of 250W;
[0089] S41. Use a micropipette to disperse 40 μL of a mixed solution of 10 wt% water-based Nafion ionomer (DuPont, USA) and ethanol in a volume ratio of 1:15 on the Pt / p-WO3 film, and dry it in an oven at 60°C for 36 hours to obtain a Pt / p-WO3 anode catalyst layer.
[0090] Based on the above-mentioned Pt / p-WO3 anode catalyst layer, this embodiment also provides a method for preparing a fuel cell, comprising the following steps:
[0091] 530 mg of 40 wt% Pt / C, 2600 mg of 10 wt% water-based Nafion ionomer and 8000 mg of isopropyl alcohol (IPA) were mixed for 15 min to obtain Pt / C slurry. The Pt / C slurry was coated on the surface of a polyimide membrane with a thickness of 25 μm using a 150 μm wire rod and dried at 70 ° C for 24 h to obtain a Pt / C cathode catalyst layer; the Pt / p-WO3 anode catalyst layer and the Pt / C cathode catalyst layer were cut into 5×5 cm 2 The cell area. At 130°C and 380kPa, the proton exchange membrane (Gore 8μm membrane), Pt / p-WO3 anode catalyst layer, and Pt / C cathode catalyst layer were hot pressed to prepare a membrane electrode; the obtained membrane electrode and diffusion layer (Toray carbon paper Toray GDL gas diffusion layer 055) and sealing ring were assembled into a single cell test fixture to obtain a single cell.
[0092] Example 3
[0093] This embodiment provides a method for preparing an anode catalyst layer, comprising the following steps:
[0094] S11, 2000 mg of WO3 nanopowder was mixed with 20000 mg of anhydrous ethanol, and ultrasonically dispersed for 60 min to obtain WO3 slurry; the WO3 slurry was coated on the surface of a polyimide film with a thickness of 25 μm using a scraper, and then dried in an oven at 80° C. for 30 h to obtain a WO3 thin film;
[0095] S21, subjecting the WO3 film to Ar plasma surface treatment to generate oxygen vacancies in the WO3 lattice to obtain a p-WO3 film; wherein the RF plasma power is 200 W, the Ar flow rate is 10 sccm, and the chamber pressure is set to 30 mTorr;
[0096] S31, placing the p-WO3 film in a deposition chamber of a customized plasma enhanced atomic layer deposition device (PEALD), under vacuum conditions, using a precursor pulse of 0.1s consisting of PEALD and trimethyl(methylcyclopentadienyl)platinum(IV) (MeCpPtMe3), adsorbing trimethyl(methylcyclopentadienyl)platinum(IV) onto the surface of the p-WO3 film, filling the deposition chamber with Ar gas for 80s of purge, introducing O2 plasma into the deposition chamber to react with trimethyl(methylcyclopentadienyl)platinum(IV) for adsorption, and obtaining a p-WO3 film containing a deposited platinum layer, filling the deposition chamber with Ar gas for 80s of purge, and repeating the above steps to obtain a Pt / p-WO3 film having a preset platinum layer thickness; wherein, O2 plasma is generated using O2 (50sccm) with a radio frequency plasma power of 250W;
[0097] S41. Use a micropipette to disperse 40 μL of a mixed solution of 10 wt% water-based Nafion ionomer (DuPont, USA) and ethanol in a volume ratio of 1:20 on the Pt / p-WO3 film, and dry it in an oven at 80°C for 36 hours to obtain a Pt / p-WO3 anode catalyst layer.
[0098] Based on the above-mentioned Pt / p-WO3 anode catalyst layer, this embodiment also provides a method for preparing a fuel cell, comprising the following steps:
[0099] 530 mg of 40 wt% Pt / C, 2600 mg of 10 wt% water-based Nafion ionomer and 8000 mg of isopropyl alcohol (IPA) were mixed for 15 min to obtain Pt / C slurry. The Pt / C slurry was coated on the surface of a polyimide membrane with a thickness of 25 μm using a 150 μm wire rod and dried at 70 ° C for 24 h to obtain a Pt / C cathode catalyst layer; the Pt / p-WO3 anode catalyst layer and the Pt / C cathode catalyst layer were cut into 5×5 cm 2 The cell area. At 130°C and 380kPa, the proton exchange membrane (Gore 8μm membrane), Pt / p-WO3 anode catalyst layer, and Pt / C cathode catalyst layer were hot pressed to prepare a membrane electrode; the obtained membrane electrode and diffusion layer (Toray carbon paper Toray GDL gas diffusion layer 055) and sealing ring were assembled into a single cell test fixture to obtain a single cell.
[0100] Comparative Example
[0101] This comparative example provides a method for preparing a Pt / C anode catalyst layer, comprising the following steps:
[0102] 530 mg of 40 wt% Pt / C, 2600 mg of 10 wt% water-based Nafion ionomer and 8000 mg of isopropyl alcohol (IPA) were mixed for 15 min to obtain Pt / C slurry. The Pt / C slurry was coated on the surface of a polyimide membrane with a thickness of 25 μm using a 150 μm wire rod and then dried at 70°C for 24 h to obtain a Pt / C anode catalyst layer.
[0103] Based on the above Pt / C anode catalyst layer, this comparative example also provides a method for preparing a fuel cell, comprising the following steps:
[0104] 530 mg of 40 wt% Pt / C, 2600 mg of 10 wt% water-based Nafion ionomer and 8000 mg of isopropyl alcohol (IPA) were mixed for 15 min to obtain Pt / C slurry. The Pt / C slurry was coated on the surface of a polyimide membrane with a thickness of 25 μm using a 150 μm wire rod and dried at 70 ° C for 24 h to obtain a Pt / C cathode catalyst layer; the Pt / C anode catalyst layer and the Pt / C cathode catalyst layer were cut into 5×5 cm2 The cell area. At 130°C and 380 kPa, the proton exchange membrane (Gore 8μm membrane), Pt / C anode catalyst layer, and Pt / C cathode catalyst layer were hot pressed to prepare a membrane electrode; the obtained membrane electrode and diffusion layer (Toray carbon paper Toray GDL gas diffusion layer 055) and sealing ring were assembled into a single cell test fixture to obtain a single cell.
[0105] The particle sizes of the platinum particles in the anode catalyst layer prepared in the examples and comparative examples before and after the reaction were measured, and the single cell performance of the fuel cells prepared in the examples and comparative examples was tested. The results are shown in Table 1.
[0106] Table 1 Particle size of platinum particles in the anode catalyst layer before and after the reaction and single cell performance of the fuel cell
[0107]
[0108] Figure 2 This is a reverse polarization curve diagram of the Pt / p-WO3 anode catalyst layer provided in Example 1 of the present application.
[0109] Depend on Figure 2 It can be seen that the anode gas hydrogen is converted into nitrogen, and the anode catalyst layer anti-reverse polarity time is measured. The single cell using the P-WO3 catalyst layer can maintain a voltage higher than -1.5V for at least 180 minutes even under reverse polarity conditions, indicating that the hydrogen overflow effect of the tungsten oxide catalyst layer and WO3 makes the anode catalyst layer have strong anti-reverse polarity ability and corrosion resistance.
[0110] Figure 3 Polarization curve diagram of the anode catalyst layer provided for Example 1 and the comparative example of the present application.
[0111] Depend on Figure 3 It can be seen that the single cell test performance of Pt / P-WO3 anode catalyst membrane electrode is better than that of Pt / C anode catalyst membrane electrode. At the rated power density of 2000 electrical density, the performance of Pt / P-WO3 membrane electrode is 0.665V, and the performance of Pt / C membrane electrode is 0.616V.
[0112] In addition, one or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0113] (1) In the embodiment of the present invention, WO3 is used as the anode catalyst carrier. WO3 can produce tungsten bronze (H x WO3), H xThe decomposition of WO3 can provide additional hydrogen ions and electrons, which can avoid insufficient hydrogen supply to the anode, thereby preventing the single cell voltage from being lower than zero volts (reverse pole), thereby avoiding severe corrosion of the anode catalyst and greatly improving the durability of the catalyst.
[0114] (2) In the embodiment of the present invention, H x WO y Can also be used as oxygen scavenger: 4H x WO y +xO2→4WO y +2xH2O, removes oxygen that penetrates into or passes through the anode, avoids unstable battery potential and prevents cathode corrosion.
[0115] (3) In the embodiment of the present invention, plasma surface treatment can solve the problem of high resistance of WO3 and avoid the problem that the low conductivity of metal oxides may cause initial performance degradation. At the same time, plasma surface treatment breaks the inert state of WO3, thereby improving the surface reactivity of WO3 and facilitating the deposition of Pt.
[0116] (4) In the embodiment of the present invention, the plasma enhanced atomic layer deposition method provided ensures that Pt is evenly distributed on the nanoscale and maximizes the catalytic activity under the premise of using a small amount of precious metal Pt. Therefore, the Pt / p-WO3 anode catalyst layer synthesized by the plasma enhanced atomic layer deposition method has the advantages of low cost, high performance and long durability.
[0117] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing an anode catalyst layer, characterized in that: The method comprises: Obtain WO3 thin film; activating the WO3 film to generate oxygen vacancies in the WO3 lattice to obtain a p-WO3 film; Depositing Pt nanoparticles on at least a portion of the surface of the p-WO3 film to obtain a Pt / p-WO3 film; The ionic polymer solution is dispersed into the Pt / p-WO3 thin film to obtain a Pt / p-WO3 anode catalyst layer.
2. The method according to claim 1, characterized in that The method of obtaining the WO3 thin film comprises: Mixing WO3 nanopowder with anhydrous ethanol to obtain WO3 slurry; The WO3 slurry is coated on at least a portion of the surface of the base film, and then dried to obtain a WO3 thin film.
3. The method according to claim 2, characterized in that The mass ratio of the WO3 nano powder to the anhydrous ethanol is 1:1 to 1:
10.
4. The method according to claim 1, characterized in that The activation adopts plasma surface treatment.
5. The method according to claim 4, characterized in that The plasma gas source of the plasma surface treatment includes one or more of O2, Ar, H2 and N2, and the plasma surface treatment includes the following parameters: the flow rate of the plasma gas source is 10sccm~30sccm, the RF plasma power is 150W~200W, and the chamber pressure is ≤30mTorr.
6. The method according to claim 1, characterized in that The step of depositing Pt nanoparticles on at least a portion of the surface of the p-WO3 film to obtain a Pt / p-WO3 film comprises: Placing the p-WO3 film in a deposition chamber of a plasma enhanced atomic layer deposition device; Under vacuum conditions, adsorbing a platinum precursor onto the surface of the p-WO3 film; Filling the deposition chamber with an inert gas for purging; Passing an oxygen precursor into the deposition chamber to undergo an adsorption reaction with the platinum precursor to obtain the p-WO3 film containing a deposited platinum layer; Filling the deposition chamber with an inert gas for purging; The above steps are repeated to obtain a Pt / p-WO3 thin film with a set platinum layer thickness.
7. The method according to claim 6, characterized in that The platinum precursor is trimethyl(methylcyclopentadienyl)platinum, and the oxygen precursor is O2 plasma.
8. The method according to claim 6, characterized in that The temperature of the deposition chamber is 120°C to 160°C, and the temperature of the platinum precursor is maintained at 65°C to 85°C.
9. An anode catalyst layer prepared by the method according to any one of claims 1 to 8.
10. A fuel cell, characterized in that: The fuel cell comprises the anode catalyst layer according to claim 9.
Citation Information
Cited By
Tungsten oxide supported palladium-silver catalyst with high specific surface area as well as preparation method and application of tungsten oxide supported palladium-silver catalyst
CN120497362A
